Information Security Applications 16th International Workshop, WISA 2015, Jeju Island, Korea, August 20-22, 2015, Revised Selected Papers - Kim, Ho-won.; Choi, Dooho; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book constitutes the thoroughly refereed post-workshop proceedings of the 16th International Workshop on Information Security Applications, WISA 2015, held on Jeju Island, Korea, in August 2015. The 35 revised full papers presented in this volume were carefully reviewed and selected from 78 submissions. The papers are organized in topical sections such as hardware security; cryptography, side channel attacks and countermeasures; security and threat analysis; IoT security; network security; cryptography; application security.
Keywords: Computer science; Computer communication systems; Computer security; Data encryption (Computer science).; Management information systems; Computer Science; Systems and Data Security; Data Encryption; Computer Communication Networks; Management of Computing and Information Systems; Electronic books